Providing vouchers and value information for already free eye exams increases uptake among a low‐income minority population: A randomized trial. (15th December 2021) - Kacker, Seema; Macis, Mario; Gajwani, Prateek; Friedman, David S.
Abstract: We study whether vouchers without and with value information encourage attendance of already free follow‐up appointments among low‐income minority individuals referred for evaluation of possible eye disease. Between May 2017 and September 2018, 821 individuals referred from 114 screening events across Baltimore City were offered (1) standard referral for a free follow‐up appointment and prescription glasses, (2) a paper voucher described as redeemable for free follow‐up and prescription glasses, or (3) an otherwise identical paper voucher which also indicated the monetary value of the appointment ($250). Under all three conditions, all referred individuals received the same patient education, counseling, and appointment reminders. We find that vouchers without and with value information increase follow‐up by 12.5 and 20.3 percentage points, respectively, corresponding to a 36% and 58% increase compared to the standard referral for free follow‐up (i.e., without a voucher). We conclude that using vouchers is a promising, low‐cost approach to increase uptake of already free health services, particularly when the vouchers also provide value information.